Consequences of barriers to primary health care for children in Aotearoa New Zealand - Mona Jeffreys; Kirsten Smiler; Lis Ellison Loschmann; Megan Pledger; Jonathan Kennedy; Jacqueline Cumming (Elsevier, 2022)
Inequities in the provision of accessible primary health care contribute to poor health outcomes and health inequity. This study evaluated inequities in the prevalence and consequences of barriers that children face in seeing a general practitioner (GP) in Aotearoa New Zealand. We analysed data on 5,947 children from the Growing Up in New Zealand longitudinal study cohort on barriers to seeing a GP in the previous year, reported by mothers when their children were aged 24 months and 54 months (in 2011/12 and 2013/14 respectively); and maternal-reported hospitalisations in the year prior to age 54 months. We used logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CIs) for consequences of these barriers.Overall, 4.7% (n = 279) of children experienced barriers to seeing a GP in the year to 24 months and 5.5% (n = 325) in the year to 54 months. At each age, and for each specific barrier studied, barriers were more prevalent among Māori (the indigenous people of Aotearoa New Zealand), and among Pacific, compared to New Zealand European, children. Children facing barriers in the year to age 24 months were twice as likely to be hospitalised in the year to 54 months (OR 2.18, 95%CI: 1.38 to 3.44). When this relationship was analysed by ethnicity, the association was strongest for Māori (OR: 2.92, 95%CI: 1.60 to 5.30), less strong for Pacific (OR 2.01, 95%CI: 0.92 to 4.37) and not present for New Zealand European (OR 1.27, 95%CI 0.39 to 4.12) families.Barriers that children face to seeing a GP have social and cost implications for families and the health system. Changes to the health system, and future health policy, must align with the New Zealand government's obligations under Te Tiriti o [The Treaty of] Waitangi, to ensure that health equity becomes a reality for Māori.